Traveling Image of the Holy Child of Atocha (Santo Niño de Atocha), Plateros, Mexico - Hughes, Jennifer Scheper (Conversations, 2014)
Each year, certain special religious images are ceremonially brought from Mexico and Central America to visit Catholic devotional communities in Southern California. These devotional statues of Catholic saints are “imágenes peregrinas,” pilgrim or traveling images.